UNSUR BUDAYA MINANGKABAU DALAM NOVEL HIDUP ADALAH PERJUANGAN KARYA AZWAR SUTAN MALAKA - Weny Maidwanti; Abdurahman Abdurahman; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
This article aim to deskription (1) relation unsure, (2) estate unsure, (3) marriage unsure to be found in novel Hidup adalah Perjuangan by Azwar Sutan Malaka. The data of this study is copy or words written of object that direct to Minangkabau culture. This research use approximation sociology literature. The results of this research are (1) relation in Minangkabau is matrilineal relation. In the matrilineal system, women have fuction like the joint heirs of tribe and have estate, (2) in tradision Minangkabau, estate dont to sell, but the women do sell estate, so that appear a problem, and (3) marriage in Minangkabau have two arrangement , based on religion and tradision. Based on religion is talk marriage settlement, but based on tradision is follow some marriage manners , that is a propose, marriage and manjapuik marapulai. And if happened separation, dead separated or life separated, so according tradision a man beck to home with family.